Sexual exploitation and violence of prostituted children - Bagong Suyanto; Medhy Aginta Hidayat; Rendy Pahrun Wadipalapa (Masyarakat, Kebudayaan dan Politik, 2020)
This study examines sexual exploitation and violence against prostituted children in East Java, Indonesia. Children who are involved in the commercial sex industry are generally prone to become victims of exploitation, violent acts, and other child abuse. This case study employs a qualitative research method to examine the various hardships experienced by prostituted children in East Java, Indonesia. The researchers interviewed ten prostituted children, seven “grey chickens” (female high school students doubling as prostituted children), eight former prostituted children, five pimps, eight procurers, and seven male customers in Surabaya City and Pasuruan Regency. This study found that, in the Indonesian commercial sex industry, prostituted children generally experience severe exploitation and violent acts. The children’s struggle to survive in the Indonesian prostitution business is a challenging condition because of their weak bargaining position: their subordinate status in the Indonesian patriarchal ideology, their weak position as children confronting adults, as well as their low socioeconomic position. The efforts to make policies to prevent exploitation and violence against prostituted children by the government and non-government agencies thus should take into account the conditions of the prostituted children as well as the driving factors for the child prostitution business that takes place in Indonesia.